Model Fuzzy Goal Programing untuk Mengoptimalkan Produksi Keripik Singkong Pada Masa Pandemi Covid-19 - Suri, Indah Resti Ayuni; Budianti, Era (LPPM Institut Pendidikan Nusantara Global, 2024)
The The obstacling that faced by the industry today is the less maximum results from allocating material sources for production and optimizing production results. The Covid-19 pandemic has influenced in the homemade cassava chip business being less developed and increasingly experiencing setbacks. The business owners are not ready to face a pandemic situation which makes one of the obstacles less than optimal in terms of income. The right modeling technique can result in satisfaction with the desired production results and income which are wanted. In this research, The problem of optimizing production is solved by using fuzzy goal programming model. This model does not need to use goal weighting so that the optimal solution is only based on the desired target. In the decision making in this research using Lingo 18.0 application which in its solution is not necessary using overtime and easy to use. This research will be carried out in two homemade industries of cassava chips, those are namely Lestari Jaya and Berkah Jaya Abadi. Based on the calculating simulation on optimizing the production of two homemade cassava chip industries in East Lampung Regency, the results obtained are more optimal by using the fuzzy goal programming model.